Validation of ethnoscience-based interactive e-module on heat transfer in traditional coffee processing - Enni Maria; Friska Octavia Rosa; Dasrieny Pratiwi; Nyoto Suseno (Educenter : Jurnal Ilmiah Pendidikan, 2026)
Students’ science process skills remain low due to theoretical, non-contextual teaching materials, especially in heat transfer topics, which indicates the need for innovative, ethnoscience-based learning resources. This study is unique in integrating ethnoscience, interactive e-modules, and traditional coffee processing context for junior high school heat transfer learning. The method used is Research and Development (R&D) with a 4D (Define, Design, Develop, Disseminate) model, limited to the develop stage. The research subjects involved Six experts (material, media, and science process skills) validated the module using standardized instruments. Data was collected through expert validation sheets and analyzed descriptively, quantitatively, and qualitatively. Data was collected through expert validation sheets and analyzed descriptively, quantitatively, and qualitatively. The validation results showed that the e-module obtained a high category in the media aspect (67.08%), material (65.83%), and very high in the science process skills facilitation aspect (86.67%). These scores indicate that the e-module meets the high feasibility criteria, particularly in facilitating students’ science process skills. Based on these results, the e-module was declared suitable for use as contextual teaching materials that can facilitate students’ scientific skills. Further studies should examine its practicality and effectiveness in classroom settings.